FINANCIAL POLICY, BUDGET REVENUES AND TAX AREAS (World Economics and Finance Bulletin, 2023)
The article examines one of the most pressing issues today - the financial sustainability of local budgets. The role of local budgets in the allocation of public funds and the development of social infrastructure in the implementation of economic and social tasks at the national level is highlighted. Based on the findings, proposals and recommendations were made to increase local budget revenues, achieve budget independence and find solutions to socio-economic issues
Keywords: financial adequacy of local budgets; socio-economic significance of local budgets; formation of financial resources of local budget